Influence of age, sexual maturation, anthropometric variables and body composition on flexibility - Keila Donassolo Santos; Abdallah Achour Junior; Roberto Régis Ribeiro; Giseli Minatto (Universidade Federal de Santa Catarina, 2010)
Since flexibility is an important component of health-related physical fitness at all ages, this parameter should be evaluated in chi ldren and adolescent s because the abi l ity to acquire and maintain levels of flexibility is greater in this age group. Thus, the objective of this study was to evaluate body weight, height, BMI and flexibility according to chronological age and sexual maturat ion and to determine the influence of these var iables on flexibi l ity in student s f rom publ ic and private schools. A cross-sectional descriptive and analytical study was conducted. The sample consisted of 2604 girls aged 8 to 17 years. Body weight, height, BMI, sexual maturation, and flexibility were evaluated. The data were analyzed descriptively using the following inferential tests: two-way analysis of variance (ANOVA) followed by the Tukey post-hoc test, Pearson's and Spearman's simple correlation coefficients, and stepwise multiple regression analysis. The SPSS® 13.0 program was used for all statistical analyses, with a level of significance of p<0.05. Significant differences with increasing age and maturation stage were observed for the variables body weight, height and BMI when compared to the subsequent year. In conclusion, body wei-ght and height increased with increasing age, especially between 8 and 13 years, and flexibility remained stable throughout childhood and adolescence.